Corona mortis injury during anterior vaginal wall suspension: A case report - Christine Herforth; Laura Stevens; Philippe E. Zimmern (Elsevier, 2024)
The corona mortis is a variant vascular anastomosis that crosses behind the superior pubic ramus connecting the external and internal iliac vessels. Its location with respect to key landmarks in the retropubic space varies. This case demonstrates a life-threatening hemorrhage following an anterior vaginal wall suspension due to needle passer injury of the corona mortis successfully managed with endovascular embolization. Surgeons operating in the retropubic space need to be cognizant of this vascular variant and potential for significant bleeding when injured. Prompt vascular control either endovascularly or with open exploration is critical in preventing patient mortality.